Effect of Shoot Pruning on Growth, Flowering and Fruiting Characteristics of Different Guava (Psidium Guajava L.) Cultivars. Issue 1 (31st December 2022) - G M, Santhoshkumar; Bhowmick, Nilesh; Chakraborty, Aditi; Dey, Amarendra Nath; Ghosh, Arunava; Dutta, Puspendu; Deb, Prahlad; Chamling, Novin; Sherpa, Nim Tshering; Senjam, Bidyarani Devi
ABSTRACT: A field trial was conducted to study the effect of shoot pruning on growth, flowering and fruiting characteristics of different guava cultivars. The experiment was carried out during Jan. 2018 to June 2019. The experiment was laid out in Randomized Block Design (RBD) with seven cultivars as treatments including L-49 (T1 ), Allahabad Safeda (T2 ), Baruipur (T3 ), Doodh Khaja (T4 ), Kafri (T5 ), Bhagalpur (T6 ) and Harichal (T7 ). Shoot pruning in guava is an alternative practice used to control the excessive growth and vigor of the plant. The plants were pruned from 120 cm above the ground level as heading back to facilitate the production of new shoots from below the cut point and allow the primary shoots. These results revealed that, guava cultivar baruipur was best in terms of number of primary shoots (58.17), length of primary shoots (135.82 cm) at 12 months after pruning, flowering percentage (66.11%) and better fruit characteristics.